Clonal relationships of memory B cell subsets in autoimmune mice - Aranburu, Alaitz; Engström, Erik; Gerasimcik, Natalija; Alsén, Samuel; Camponeschi, Alessandro; Yrlid, Ulf; Grimsholm, Ola; Mårtensson, Inga-Lill (Frontiers in Immunology, 2023)
Immunological memory protects our body from re-infection and it is composed of a cellular and a humoral arm. The B-cell branch with its memory B cells (MBCs), plasma cells and antibodies, formed either in a germinal centre (GC) -dependent or -independent manner, ensure that we can rapidly mount a recall immune response. Previous work in immunised wildtype (WT) mice have identified several subsets of MBCs whereas less is known under autoimmune conditions. Here, we have investigated the heterogeneity of the MBC compartment in autoimmune mouse models and examined the clonal relationships between MBC subsets and GC B cells in one of the models. We demonstrate the presence of at least four different MBC subsets based on their differential expression pattern of CD73, CD80 and PD-L2 in surrogate light chain-deficient (SLC-/-), MRL+/+ and MRLlpr/lpr mice, where most of the MBCs express IgM. Likewise, four MBC subsets could be identified in WT immunised mice. In SLC-/- mice, high-throughput sequencing of Ig heavy chains demonstrates that the two CD73-positive subsets are generally more mutated. Lineage tree analyses on expanded clones show overlaps between all MBC subsets and GC B cells primarily in the IgM sequences. Moreover, each of the three IgM MBC subsets could be found both as ancestor and progeny to GC B cells. This was also observed in the IgG sequences except for the CD73-negative subset. Thus, our findings demonstrate that several MBC subsets are present in autoimmune and WT mice. In SLC-/- mice, these MBC subsets are clonally related to each other and to GC B cells. Our results also indicate that different MBC subsets can seed the GC reaction.